Differential organization of male copulatory patterns in high- and low-yawning-frequency sublines versus outbred Sprague–Dawley rats - Eguibar, Jose R.; Cortes, Carmen; Toriz, Cesar G.; Romero-Carbente, Jose C.; González-Flores, Oscar; Fernández-Guasti, Alonso (Physiology & behavior, 2016)
The temporal organization of masculine sexual behavior in rats is highly stereotyped; involving a sequence of mounts, intromissions and ejaculations. Sexual behavior has been described in exogamic and genetically manipulated rodent species. In this work, we compare the male sexual behavior of outbred Sprague–Dawley (SD) to those of rats inbred for high (HY)- and low (LY)- spontaneous yawning frequency. In the first experiment, the percentage of inexperienced rats' ejaculatory behavior is significantly lower in the HY and LY respect to Sprague–Dawley rats. The latency to ejaculate for inexperienced HY was shorter than the LY and SD rats. In the second experiment, we examined the differences between inbred sublines and Sprague–Dawley rats once the subjects had become sexually experienced after four copulatory sessions. HY rats still have slower proportion of ejaculators respect to LY and SD rats. Additionally, postejaculatory latencies were longer for HY rats, with longer intercopulatory intervals and higher number of copulatory bouts that delayed ejaculation. Both sublines show lower copulatory efficiency respect to SD rats. In conclusion, both sublines show alterations in the temporal organization of sexual motor pattern that are due at least partially to strong inbreeding process to select them •The learning rate for male sexual behavior is slower in the high-yawning rats.•Inbreeding affects sexual performance in high-yawning rats.•The percentage of non-copulators and sluggish rats is higher in high-yawning rats.•High-yawning rats are less motivated to copulate.•High-yawning rats had more penile erections but a deficient copulatory display.